Integrated biomarker for type 2 diabetes mellitus and impaired fasting glucose based on metabolomics analysis using ultra‐high performance liquid chromatography quadrupole‐Orbitrap high‐resolution accurate mass spectrometry. (14th April 2020) - Long, Jianglan; Liu, Liwei; Jia, Qingquan; Yang, Zhirui; Sun, Zhi; Yan, Can; Yan, Dan
Abstract : Rationale: The prevalence of type 2 diabetes mellitus (T2DM) is increasing but its early diagnosis in high risk populations remains challenging using only fasting blood glucose (FBG) or hemoglobin A1c measurements. It is, therefore, important to search for an integrated biomarker for early diagnosis by determining metabolites associated with the progression of the disease. Methods: We recruited 149 participants (51 T2DM patients, 50 individuals with impaired fasting glucose (IFG) and 48 normal glucose tolerance subjects). Their serum samples were analyzed based on a metabolomics approach using ultra‐high‐performance liquid chromatography quadrupole‐Orbitrap high‐resolution accurate mass spectrometry (UHPLC/Q‐Orbitrap HRMS). The changes in metabolites were profiled and evaluated using univariate and multivariate analyses. Furthermore, a biomarker model was established and the potential biomarkers were evaluated using binary logistic regression analysis and receiver operating characteristic analysis with AUC (area under the curve). Pathway analysis of differential metabolites was performed to reveal the important biological information. Results: Thirty‐eight differential metabolites were identified as significantly associated with T2DM patients and 23 differential metabolites with IFG individuals, mainly amino acids, carnitines, and phospholipids. By evaluating 17 potential biomarkers, we defined a novel integrated biomarker consisting of 2‐acetolactate, 2‐hydroxy‐2, 4‐pentadienoate, L‐arabinose and L‐glutamine. The AUCs of the integrated biomarker with IFG and T2DM patients were 0.874 and 0.994, respectively, which showed a superior diagnostic performance. The levels of 2‐acetolactate and 2‐hydroxy‐2, 4‐pentadienoate were strongly positively correlated with FBG, while L‐glutamine and L‐arabinose were strongly negatively associated with FBG. After pathway analysis, it was suggested that the majority of the influenced metabolic pathways associated with diabetes referred to amino acid metabolism. Conclusions: The integrated biomarker could diagnose IFG and T2DM with a superior diagnostic performance. This finding provides support for novel biomarkers in the diagnosis and treatment of diabetes.